Characteristics of patients with suspected COVID-19 infection and the outcome of a visit to a Covid-outpatient clinic - Petrov Kiurski, Miloranka (General Practice, 2025)
Introduction. The COVID-19 patients were treated in outpatient clinics at primary healthcare centers, which alleviated the pressure on secondary and tertiary healthcare levels. Objective. We aimed to research the characteristics of COVID patients, such as their symptoms, test results, comorbidities, and exam outcomes. Method. We completed a questionnaire for patients who attended for examination between April 23 and April 29, 2021. We collected data on gender, age, symptoms, comorbidities, vaccination status, and examination outcomes. The data were statistically analyzed using the SPSS program. Results. A total of 222 participants, comprising 61.7% women, were involved in the study, with an average age of 47.9 ± 15.2 years. Among them, 24.8% were vaccinated, and 60.4% tested positive for COVID-19. The most common symptoms reported included malaise, muscle and joint pain, cough, and fever. Approximately half of the participants had comorbidities, primarily among older individuals. Statistical analysis showed no significant correlation between COVID- 19 test results and vaccination status (p=0.099), nor was there a significant relationship with the presence of comorbidities (p=0.118). Patients exhibiting milder symptoms were typically sent home, while 26.1% were referred for further diagnostic testing, and 10.4% were admitted to the hospital. Vaccination status did not appear to influence the outcome of the visits (p=0.240). Participants aged 51 to 65 were most frequently referred for further diagnostics, while those over 65 (p=0.004) and individuals with comorbidities (p=0.003) were more likely to be hospitalized. Conclusion. There was no significant difference in positive COVID-19 test results regarding vaccination and comorbidities. Only 10% of the patients were referred to the hospital, primarily those over 65 and patients with comorbidities.